Da mediação à incorporação social: lugar e ação da intelectualidade na América Central contemporânea - Fred Maciel (Nuevo mundo - Mundos Nuevos, 2021)
This text aims to expose considerations to think about the place and the role of the intellectuality in contemporary times, especially in the Central American region – a space marked by the performance of literate figures engaged in past decades. Through scoring about the regional context and the historical relations around the topics of incorporation and social participation, it would be possible to reflect on the plausible maintenance of a leading role of the intellectuals in the midst of the current democratic panorama.